2021
DOI: 10.1101/2021.08.05.21261564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Injection Drug use Practices and HIV infection among People Who Inject Drugs in Kigali, Rwanda

Abstract: Background In Rwanda, epidemiological data characterizing people who inject drugs (PWID) and their burden of HIV are limited. We examined injecting drug use (IDU) history, practices, and HIV infection in a sample of PWID in Kigali. Methods From October 2019–February 2020, 322 PWID aged >18 were enrolled in a cross–sectional study using convenience sampling in Kigali. Participants underwent a structured interview and HIV testing. We used Poisson regression with robust variance estimation to assess IDU practi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While curbing the infections and transmission of HIV among MSM and sex workers are speci cally mentioned, Rwanda's national HIV/AIDS targets do not make mention of transgender people and do not prioritize interventions among IDUs -because "injection drug use is not present or widely practiced in Rwanda" [5]. However, recent studies have shown that 10% of transgender women and 9.5% of IDUs in Kigali were HIV positive [10,11].…”
Section: Hiv Services Challenges and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While curbing the infections and transmission of HIV among MSM and sex workers are speci cally mentioned, Rwanda's national HIV/AIDS targets do not make mention of transgender people and do not prioritize interventions among IDUs -because "injection drug use is not present or widely practiced in Rwanda" [5]. However, recent studies have shown that 10% of transgender women and 9.5% of IDUs in Kigali were HIV positive [10,11].…”
Section: Hiv Services Challenges and Facilitatorsmentioning
confidence: 99%
“…The HIV rates among these groups continue to rise and remain high globally and in Rwanda [5,6]-with a country-wide HIV prevalence of 51% among commercial sex workers, over 10% among prisoners, and 4.8% among MSM [7,8,9]. As for transgender women and injection drug users in Kigali, the prevalence stands at 10% and 9.5% respectively [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of information about these KP groups is concerning and points to a larger issue within the healthcare system. While curbing the HIV infections among MSM and sex workers are specifically mentioned, Rwanda's national HIV/AIDS targets do not make mention of transgender people and do not prioritize interventions among IDUs-because "injection drug use is not present or widely practiced in Rwanda" [5], despite recent studies showing that 10% of transgender women and 9.5% of IDUs in Kigali were HIV positive [10] [11].…”
Section: Lack Of Data On Injection Drug Users and Transgender Peoplementioning
confidence: 99%
“…However, opposite trends exist among the key populations (KP)-sex workers, men who have sex with men (MSM), prisoners, transgender individuals, and injection drug users. The HIV rates among these groups continue to rise and remain high globally and in Rwanda [5] [6]-with a country-wide HIV prevalence of 51% among commercial sex workers, 4.8% among MSM, and over 10% among prisoners, transgender women, and injection drug users [7] [8] [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%